Effect of polypharmacy on plasma bepridil concentration in patients with heart failure: a multicenter retrospective study - Yuki Asai; Hiroki Arihara; Saki Omote; Ena Tanio; Saena Yamashita; Takashi Higuchi; Ei Hashimoto; Momoko Yamada; Hinako Tsuji; Yoshihiro Kondo; Makoto Hayashi; Yoshiaki Yamamoto (BMC, 2023)
Abstract Background Polypharmacy, defined as the concurrent use of over six drugs, is common in the treatment of heart failure (HF); however, unpredictable drug interactions with bepridil may occur. In this study, we have elucidated the influence of polypharmacy on plasma bepridil concentrations in patients with HF. Methods We conducted a multicenter retrospective study involving 359 adult patients with HF who received oral bepridil. Because QT prolongation is an adverse effect following plasma bepridil concentrations ≥800 ng/mL, the risk factors for patients achieving these concentrations at steady state were elucidated via multivariate logistic regression. The correlation between bepridil dose and plasma concentration was examined. The effect of polypharmacy on the value of the concentration-to-dose (C/D) ratio was investigated. Results A significant relationship was observed between bepridil dose and plasma concentration (p <  0.001), and the intensity of the correlation was moderate (r = 0.503). Based on multivariate logistic regression, the adjusted odds ratios for a daily dose of bepridil ≥1.6 mg/kg, polypharmacy, and concomitant of aprindine, a cytochrome P450 2D6 inhibitor, were 6.82 (95% coefficient interval: 2.104-22.132, p = 0.001), 2.96 (95% coefficient interval: 1.014-8.643, p = 0.047), and 8.63 (95% coefficient interval: 1.684-44.215, p = 0.010), respectively. Despite the moderate correlation in non-polypharmacy, the correlation was not observed in polypharmacy. Therefore, inhibiting metabolism, along with other mechanisms, may contribute to the polypharmacy-induced increase in plasma bepridil concentrations. Moreover, the C/D ratios in the groups receiving 6-9 and 10≤ concomitant drugs were 1.28- and 1.70-fold higher than in those receiving <6 drugs, respectively. Conclusions Plasma bepridil concentrations may be influenced by polypharmacy. Moreover, the plasma bepridil concentration increased in correlation with the number of concomitant drugs used. Although the mechanism of this increase could not be determined, plasma bepridil concentrations should be periodically monitored for safe use in patients with HF. Trial registration Retrospectively registered.